Psychosocial factors affecting the academic peformance of UP College of Dentistry Class 1989 - Pampolina, Catherine G.; Villacorta, Ma. Elena M.; Guerrero, Leticia (Adviser).
The factors affecting the academic performance of UP College of Dentistry Class '89 were studied by correlating the general weighted average of the 44 samples and their answers to the prepared questionnaires. The factors under study are: self concept, career choice crisis, family problems, parent pressure, peer values, boy-girl relationship, and commuting. it was shown that only self-concept has a significant indirect relationship with the academic performance. The remaining factors do not have any significant effect on the academic performance of UP College of Dentistry Class '89.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental students